The use of the oxidative stress responses as biomarkers in Nile tilapia (Oreochromis niloticus) exposed to in vivo cadmium contamination - Almeida, J. A.; Diniz, Y. S.; Marques, SFG; Faine, L. A.; Ribas, B. O.; Burneiko, R. C.; Novelli, ELB (Elsevier B.V., 2002)
Water contaminants have a high potential risk for the health of populations. Protection from toxic effects of environmental water pollutants primarily involves considering the mechanism of low level toxicity and likely biological effects in organisms who live in these polluted waters. The biomarkers assessment of oxidative stress and metabolic alterations to cadmium exposure were evaluated in Nile tilapia, Oreochromis niloticus. The fish were exposed to 0.35, 0.75, 1.5, and 3.0 mg/l concentrations of Cd2+ (CdCl2) in water for 60 days. Fish that survived cadmium exposure showed a metabolic shift and a compensatory development for maintenance of the body weight gain. We observed a decreased glycogen content and decreased glucose uptake in white muscle. Lactate dehydrogenase (LDH) and creatine phosphokinase (CK) activities were also decreased, indicating that the glycolytic capacity was decreased in this tissue. No alterations were observed in total protein content in white muscle due to cadmium exposure suggesting a metabolic shift of carbohydrate metabolism to maintenance of the muscle protein reserve. There was an increase in glucose uptake, CK increased activity, and a clear increase of LDH activity in red muscle of fish with cadmium exposure. Since no alterations were observed in lipoperoxide concentration, while antioxidant enzymes glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) were changed in the liver and the red and white muscle of fish with cadmium exposure, we can conclude that oxygen free radicals are produced as a mediator of cadmium toxicity. Resistance development is related with increased activities of antioxidant enzymes, which were important in the protection against cadmium damage, inhibiting lipoperoxide formation. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: cadmium; oxidative stress; metabolic responses; fish; Oreochromis niloticus